Pengaruh BI Rate, Inflasi, Nilai Tukar Rupiah dan Harga minyak terhadap Return Harga Saham Sub-Sektor Properti (Studi pada Bursa Efek Indonesia Periode 2014-2017) - Muhammad Iqbal; Raja Masbar (Fakultas Ekonomi dan Bisnis UNSYIAH, 2019)
Abstract This study aims to analyze the influence of the BI rate, inflation, exchange rates and world oil prices on the return of shares of the property sub-sector listed on the Indonesia stock exchange for the period 2014 to 2017. The data used in this study are secondary data obtained from institutions - official institution. This data consists of monthly period data starting from January 2014 to December 2017 with a total sample of 48 observations. The model used in this study is a multiple linear regression model. This study also uses the classic assumption test including normality test, multicollinearity test, autocorrelation test and heteroscedasticity test. With the independent variables used are the BI rate, inflation, exchange rates and world oil prices. While the dependent variable used is stock price returns. The results of multiple linear regression show that the BI rate has a positive and insignificant effect on stock price returns. While inflation has no significant negative effect on stock price returns. The exchange rate shows a significant negative effect on stock price returns. And world oil prices have a significant negative effect on stock price returns.Keywords: BI rate, inflation, exchange rate, oil price, stock price return